2019
DOI: 10.3389/fimmu.2019.02135
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling as a Molecular Target by Pathogenic Bacteria

Abstract: The Wnt/β-catenin signaling pathway is crucial to regulate cell proliferation and polarity, cell determination, and tissue homeostasis. The activation of Wnt/β-catenin signaling is based on the interaction between Wnt glycoproteins and seven transmembrane receptors—Frizzled (Fzd). This binding promotes recruitment of the scaffolding protein Disheveled (Dvl), which results in the phosphorylation of the co-receptor LRP5/6. The resultant molecular complex Wnt–Fzd–LRP5/6-Dvl forms a structural region for Axin inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 78 publications
3
84
0
Order By: Relevance
“…As many as 64% (16 out of 25) of the pathways reported as overrepresented by IPA relate to the host immune response (Table 5 ). Of note, this list includes pathways related with the bidirectional host-microbial crosstalk such as ERK/MAPK signaling [ 53 ], Th1 and Th2 activation pathway [ 54 ], TGF-β signaling [ 55 ], Wnt/β-catenin signaling [ 56 ], glucocorticoid receptor signaling [ 57 ], VDR/RXR activation [ 58 ], IL-22 signaling [ 59 ], and aryl hydrocarbon receptor [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…As many as 64% (16 out of 25) of the pathways reported as overrepresented by IPA relate to the host immune response (Table 5 ). Of note, this list includes pathways related with the bidirectional host-microbial crosstalk such as ERK/MAPK signaling [ 53 ], Th1 and Th2 activation pathway [ 54 ], TGF-β signaling [ 55 ], Wnt/β-catenin signaling [ 56 ], glucocorticoid receptor signaling [ 57 ], VDR/RXR activation [ 58 ], IL-22 signaling [ 59 ], and aryl hydrocarbon receptor [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt family is constituted by a group of cysteine‐rich glycoproteins that can initiate varied signaling cascades such as the planar cell polarity pathway, the canonical pathway, and the Wnt/Ca 2+ pathway 4 . Typically, initiation and progression of CRC are closely associated with deregulation of the canonical Wnt/β‐catenin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…GO analysis and KEGG analysis demonstrated that most ncRNAs in included panels involved into Wnt signalling pathway, oxidative stress and immune cell activation and differentiation, which were closely related to the pathogenesis of TB 55‐57 . MiR‐150‐5p was selected by 3/13 miRNA panels which targeted different populations and used different sample types.…”
Section: Discussionmentioning
confidence: 99%
“…54 GO analysis and KEGG analysis demonstrated that most ncRNAs in included panels involved into Wnt signalling pathway, oxidative stress and immune cell activation and differentiation, which were closely related to the pathogenesis of TB. [55][56][57] MiR-150-5p was selected by 3/13 miRNA panels which targeted wide application ranges, especially in limited-resource regions. [66][67][68] Benefiting from the rapid development of these technologies, Large-scale prospective validation in diverse populations is a necessary step for the entry of these panels into the clinic.…”
Section: Discussionmentioning
confidence: 99%